Life cycle assessment of energy consumption and GHG emission for sewage sludge treatment and disposal: a review - Yu, Shilin; Deng, Shuanghui; Zhou, Ao; Wang, Xuebin; Tan, Houzhang (Frontiers in Energy Research, 2023)
With increasing population and urbanization, the amount of municipal sewage sludge generated is huge and growing rapidly. In order to minimize resource inputs and pollutant emissions in the sludge disposal process, it is crucial to carry out an environmental impact analysis and sustainability assessment of different strategies based on life cycle assessment (LCA). LCA provides a flexible framework for quantifying the consumption and emissions of different processes to determine the energy consumption and environmental impact of sewage sludge treatment and disposal. The aim of this review is to compare the energy consumption and GHG emissions of existing sludge management options for energy and nutrient recovery. At the same time, the characteristics of sewage sludge and the potential to convert sludge from waste to valuable products were assessed. While the excessive moisture content and ash content make sludge unsuitable for use as fuel, and the potential risk of contamination with heavy metals makes it less suitable for use as organic fertilizer, energy and material recovery during disposal can reduce disposal costs and environmental impacts. In the context of the current limitations reviewed, the level of potential GHG emissions of existing sludge treatment and disposal routes is: composting > anaerobic digestion > pyrolysis > incineration. With suitable sludge treatment routes, negative GHG emissions could potentially be achieved by substituting fossil fuels for heat and electricity generation, or as a fertilizer substitute. The development and application of future sludge management strategies should aim at reduction and harmless disposal, thereby reducing the operating costs and environmental burdens through resources.